Developing a welfare assessment protocol for Australian lot-fed cattle - Taylor, Emily; Dunston-Clarke, Emma; Brookes, Daniel; Jongman, Ellen; Linn, Benjamin; Barnes, Anne; Miller, David; Fisher, Andrew; Collins, Teresa (Frontiers in Animal Science, 2023)
Lot feeding of cattle has gained momentum in recent years to improve efficiency in meeting market demands for high quality protein. Concurrently, societal concern for the welfare of animals raised in intensive farming systems has increased. Thus, the reporting of animal health and welfare measures is a key goal for the Australian cattle lot-fed industry. Although feedlots vary in location, climate, capacity, cattle genotype, and feeding programs, many welfare concerns are applicable across the industry. Despite this, no recognised standardised animal welfare assessment protocol exists for the Australian lot-fed industry. This study aimed to identify relevant measures to develop an assessment protocol, by identifying key welfare issues and their relevant measures, considering the validity, reliability, and practicality of each when applied to the feedlot context. An advisory model was derived after reviewing the relevant literature and five international protocols for the assessment of beef cattle (Welfare Quality®, AssureWel, US Beef Quality Assurance assessment tool, Canadian Feedlot Animal Care Assessment program, and an Australian Live Export industry protocol), followed by stakeholder consultation. A total of 109 measures were evaluated, with 99 environmental-, management-, resource-and animal-based measures being proposed. Piloting of the protocol on commercial feedlots will enable further refinement and validation, to provide an evidence-based, practical protocol to facilitate standardised monitoring of cattle welfare. Such a protocol could promote continued advances in animal welfare at a feedlot level and support a sustainable industry by addressing societal concerns.